The ontogeny of appendages and carapace of Neonesidea schulzi (Ostracoda: Bairdiidae) from the Red Sea coast, Egypt. Issue 4 (2nd October 2017) - Yousef, Ebtesam A.; Moustafa, Alaa Y.
Abstract: The ostracod genus Neonesidea is broadly distributed in shallow marine waters. The ontogeny of the N. schulzi (Bairdiidae) is described in detail by studying the development of the appendages and variations in carapace form, size and structure. Neonesidea schulzi has eight post-embryonic instars, and a gap in its ontogenetic development during instar A-6, where no new Anlage is added. The Anlagen of the copulatory organs and the forked terminal claw of second antenna appear in the seventh (A-1) instar, and the first thoracic legs of podocopid ostracods are shown to descend from the thoracic region. For the first time in ostracods, observations of moulting from sixth and seventh instars are presented.